The neurobiology of circadian timing - Kalsbeek, Andries (Progress in brain research, 2012)
How rod, cone, and melanopsin photoreceptors come together to enlighten the mammalian circadian clock -- Melanopsin phototransduction: Slowly emerging from the dark -- Circadian clocks: Lessons from fish -- Two clocks in the brain: An update of the morning and evening oscillator model in Drosophila -- Circadian system from conception till adulthood -- When does it start ticking? Ontogenetic development of the mammalian circadian system -- The circadian output signals from the suprachiasmatic nuclei -- Suprachiasmatic nucleus: Cellular clocks and networks -- Dynamic neuronal network organization of the circadian clock and possible deterioration in disease -- Interaction of central and peripheral clocks in physiological regulation -- Circadian rhythms in white adipose tissue -- Circadian modulation of sleep in rodents -- Local aspects of sleep: Observations from intracerebral recordings in humans -- The circadian clock component PERIOD2: From molecular to cerebral functions -- Generation of mouse mutants as tools in dissecting the molecular clock -- In search of a temporal niche: Social interactions -- In search of a temporal niche: Environmental factors -- Feedback actions of locomotor activity to the circadian clock -- The impact of the circadian timing system on cardiovascular and metabolic function -- Nutrition and the circadian timing system -- Managing neurobehavioral capability when social expediency trumps biological imperatives -- Noisy and individual, but doable: Shift-work research in humans -- The evolutionary physiology of photoperiodism in vertebrates -- A kiss for daily and seasonal reproduction -- Circannual rhythm in the varied carpet beetle, Anthrenus verbasci -- Avian migration: Temporal multitasking and a case study of melatonin cycles in waders